Wettability Engineering: Wettability Engineering for Studying Ion Transport in 2D Layered Materials (Adv. Mater. Interfaces 3/2021). Issue 3 (5th February 2021) - Kühne, Matthias; Zhao, Dong; Zschieschang, Ute; Buck, Regina; Müller, Michaela; Klauk, Hagen; Smet, Jurgen H.
Abstract : Wettability engineering is exploited to tame an electrolyte drop and place it accurately along the perimeter of a bilayer of graphene in order to generate a peripheral galvanic cell. This is accomplished by patterning a material (red) on top of the substrate with a large contact angle difference with respect to the substrate itself. More details can be found in article number 2001453 by Jurgen H. Smet and co‐workers. The image has been created by Nils Gross.